Food science an ecological approach - Edelstein, Sari (Jones & Bartlett Learning, 2019)
Food Science: An Ecological Approach presents the field of food science―the study of the physical, biological, and chemical makeup of food, and the concepts underlying food processing―in a fresh, approachable manner that places it in the context of the world in which we live today. Specifically, the text marries food science with present concerns regarding food quality, composition, and availability, emphasizing the “ecological approach.” Section I of Food Science: An Ecological Approach presents the introductory concepts students studying food science are required to learn. These foundational chapters provide students with the background to understand the relationship between food science and the environment, research methods used by food scientists, and the underlying science and chemistry behind food composition. Section II provides a focused discussion of the types of food and the science behind each. Using a consistent presentation, each chapter discusses each food’s historical, cultural, and ecological significance; its physical and chemical properties; preparation techniques and food safety concerns; and its impact on health. New & Key Features of the Second Edition: - NEW - New case studies have been added to the end of each chapter encouraging students to apply the concepts of each case to a problem in food science - NEW & UPDATED - Ecological concerns throughout the text have been updated, and other new ecological concerns have been added, to keep students up-to-date on matters pertinent to food science ecology -NEW - Includes a new Chapter 5 on food safety -NEW - The Food Science Workbook and Lab Manual is included in the Navigate 2 platform, free with every new print copy of the print text, and includes practical exercises based on key concepts from the text--Provided by publisher.